2010
DOI: 10.4028/www.scientific.net/msf.654-656.334
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformation and Annealing Behavior of SUS 304 Austenitic Stainless Steel Deformed by High Pressure Torsion

Abstract: SUS 304 austenitic stainless steel was subjected to severe plastic deformation (SPD) by the method of high pressure torsion (HPT). From a fully austenitic matrix (γ), HPT resulted in phase transformation to give a two phase structure of austenite (γ) and martensite (α') by the transformation γα'. The phase transformation was accompanied by an increase in hardness (Hv) from 1.6 GPa in the as annealed form to 5.4 GPa in the deformed state. Subsequent annealing in temperature range 250oC to 450oC resulted in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…It was shown that charging the steels with hydrogen reduced the volume of martensite [13]. An austenite to martensite (γ → α') transformation was also reported in a SUS 304 steel processed at a low rotation rate [14]. A phase transformation in HPT was observed in an A220 steel with a composition similar to 316L steel.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was shown that charging the steels with hydrogen reduced the volume of martensite [13]. An austenite to martensite (γ → α') transformation was also reported in a SUS 304 steel processed at a low rotation rate [14]. A phase transformation in HPT was observed in an A220 steel with a composition similar to 316L steel.…”
Section: Introductionmentioning
confidence: 91%
“…In this operation, a sample in the shape of a thin disc is compressed between rigid anvils and subjected to torsional straining. Processing by HPT has been used with iron [5,6] and different steels [6][7][8][9][10][11][12][13][14][15][16], including twinning induced plasticity steels [17][18][19] which also exhibit very high uniform elongations at room temperature. A review of these data shows that different effects were reported during the processing of iron and steels by HPT.…”
Section: Introductionmentioning
confidence: 99%
“…UFG (Ultrafine-grained) as well as NG (nano-grained) materials have been produced by reversion annealing of AISI 304, AISI 304L, and less stable AISI 301LN and AISI 201 metastable stainless steels, where the material strength is enhanced with a moderate decrease in plasticity. [23][24][25][26][27][28][29] Grain refinement via reversion annealing still draws attention, i.e., Sun et al [30] reported diffusive reversion of strain-induced martensite during annealing in the range of 823 K to 923 K (550°C to 650°C). [30] This paper reports the formation of SIM during the tensile test at different temperatures, and the reverse transformation analysis by the use of DSC, in-situ X-ray diffraction, and dilatometry.…”
Section: Introductionmentioning
confidence: 99%
“…The volume fraction of deformation-induced martensite depends on different parameters, such as the applied strain, temperature, [13] initial grain size, [9,14] as well as applied stress state, and strain rate. Various techniques, such as equal channel angular pressing (ECAP), [25][26][27][28][29] high pressure torsion (HPT), [30,31] accumulative roll-bonding (ARB), [32,33] constrained groove pressing (CGP), [34] constrained groove rolling (CGR), [35] and repetitive corrugation and strengthening (RCS) [36][37][38] have been well developed. [17][18][19] Because of low SFE of AISI 304 steel (21 mJ m À2 ), [20,21] deformation bands including mechanical twins and e-martensite (hcp) are produced, which results from overlapping of stacking faults in each second {111} g plane.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Recently, severe plastic deformation (SPD) techniques for producing highly strained materials have been highly appreciated. Various techniques, such as equal channel angular pressing (ECAP), [25][26][27][28][29] high pressure torsion (HPT), [30,31] accumulative roll-bonding (ARB), [32,33] constrained groove pressing (CGP), [34] constrained groove rolling (CGR), [35] and repetitive corrugation and strengthening (RCS) [36][37][38] have been well developed.…”
Section: Introductionmentioning
confidence: 99%